2009
DOI: 10.1111/j.1464-410x.2008.08012.x
|View full text |Cite
|
Sign up to set email alerts
|

Radical prostatectomy for prostatic adenocarcinoma: a matched comparison of open retropubic and robot‐assisted techniques

Abstract: OBJECTIVETo assess the perioperative complications and early oncological results in a comparative study matching open radical retropubic (RRP) and robot‐assisted radical prostatectomy (RARP) groups.PATIENTS AND METHODSFrom August 2002 to December 2005 we identified 294 patients undergoing RARP for clinically localized prostate cancer. A comparison RRP group of 588 patients from the same period was matched 2:1 for surgical year, age, preoperative prostate‐specific antigen level, clinical stage and biopsy Gleaso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

17
174
6
9

Year Published

2010
2010
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 248 publications
(206 citation statements)
references
References 21 publications
17
174
6
9
Order By: Relevance
“…In a similar study from the Mayo Clinic with a median follow-up of 16 months, the BCR rate was not different between RALP and ORP patients (8% for both, p = 0.69)[18]. Likewise, a comparative study from Duke University with mean follow-up of approximately 1 year found no difference in BCR rates between ORP and RALP after adjusting for the effects of clinical and pathologic features (hazard ratio 0.94; 95% CI: 0.55–1.61; p = 0.82)[35].…”
Section: Comparison and Discussion Of Orp And Ralpmentioning
confidence: 99%
See 4 more Smart Citations
“…In a similar study from the Mayo Clinic with a median follow-up of 16 months, the BCR rate was not different between RALP and ORP patients (8% for both, p = 0.69)[18]. Likewise, a comparative study from Duke University with mean follow-up of approximately 1 year found no difference in BCR rates between ORP and RALP after adjusting for the effects of clinical and pathologic features (hazard ratio 0.94; 95% CI: 0.55–1.61; p = 0.82)[35].…”
Section: Comparison and Discussion Of Orp And Ralpmentioning
confidence: 99%
“…In an age- and tumor characteristic–matched comparison of 588 ORPs and 294 RALPs, researchers from the Mayo Clinic found no difference in overall complication rates[18]. One-month complication rates for the RALP group were 8% compared to 5% in the ORP group ( p = 0.064).…”
Section: Comparison and Discussion Of Orp And Ralpmentioning
confidence: 99%
See 3 more Smart Citations